The ethics of journalism challenged: The blurring boundary between local journalism and communications - Hujanen Jaana; Grönlund Mikko; Ruotsalainen Juho; Lehtisaari Katja; Vaarala Viljami (Denmark, 2023)
The article examines Finnish news professionals’ views on the ethical challenges that ensue from emerging and intertwining forms of local professional journalism and communications. Besides describing the current situation, the article employs data from a survey of editors-in-chief to investigate how news professionals anticipate the relationship between journalism and communications evolving in the future. Respondents perceived a blurring of the boundary between local journalism and communications. They observed economic pressures creating incentives for news media to compromise their journalistic ethics and ethical concerns arising from professional communications’ adoption of journalistic practices. Editors-in-chief maintained that the boundaries between journalism and other forms of communication are clear in their media but indistinct in other local news media outlets and in society in general. They predicted an ambiguous, even grim, future of local news media in Finland. However, local news media may have a positive future if they become distinct, attractive and relevant again to citizens.